Two effects of COVID-19 in Colombia: deepening inequality and a return to hyperpresidentialism - Barrera Varela, Pedro Javier (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The purpose of this article is to analyze, from a critical position, with theoretical and factual support, the changes that the Colombian legal system has undergone since the declaration of the State of Emergency.The research proposes, as a thesis, that the excessive normative increase at the head of the exceptional legislator produced two dire consequences for Colombian society: a deepening of inequality and a return tohyper-presidentialism. Thus, to support the above-mentioned thesis, three arguments were developed. First, we propose that in the Colombian context two constants persist: inequality and exclusion. To defendthis premise, we analyzed some sentences issued by the high courts and statistical data that confirms them. We also presented an X-ray of the right to health, which shows that this sector suffers from the disease ofsystemic corruption. Second, we analyzed the Colombian constitutional design and concluded that, in the current scenario, the different powers have been co-opted by the president of the republic. Third,we conducted a critical assessment of the legislative decrees issued under the state of emergency, and concluded that at least 34 decrees were unnecessary, inconvenient, or unconstitutional. The most critical aspect of the last argument was to highlight the weak role of the Constitutional Court in its exerciseof automatic control of constitutionality.